The Categorical Preference of the Mind: Assessing the Proposed Cognitive Hierarchy of Templates in CSR Using Pictorial Preference - Miller, Michael T.; Thorson, Jill 198X-; Robertson, Paul (2022)
Fundamental to the traditional, Cognitive Science of Religion (CSR) mind-based model is that the human mind perceives the world through the use of ontological categories. These categories are often defined as templates, which are associated with the recognition of basic ontological categories organized hierarchically due to evolutionarily sourced strategic connections: PERSON > ANIMAL > PLANT > ARTIFACT > OBJECT. If the field of CSR is to use such foundational concepts as MCIs, ontological categories, socially strategic and inference generation, we must first test and verify that this hierarchical ontological schema is in fact valid, especially given some recent shifts away from the mind-based model. The goal of this study was to analyze participant preferences for different aspects of the CSR mind-based model, such as template categories and socially strategic inferences. To test this, participants saw four conditions, each with a variety of images that reflected these categories and inferences. Main findings saw no preference between hypothesized template categories, preference for socially strategic images within the same category, and preference for non-threatening images over threatening images of the same category. The latter two findings (socially strategic; threat avoidance) confirm core theories and recent work in CSR; the former finding (no hierarchy preference) calls into question the nature and use of ontological categories.
Keywords: CSR theory; ontological categories; socially strategic; templates; threat avoidance